Physical Activity as a Victim, a Perpetrator, or Part of the Solution to the Climate Crisis? - Gelius, Peter; Messing, Sven; Tcymbal, Antonina; Birkholz, Leonie; Abu-Omar, Karim (Journal of Physical Activity and Health, 2024)
Humanity is facing a polycrisis, including climate change, loss of biodiversity, and economic inequalities. This commentary examines the role of physical activity (PA) research in the context of climate change, highlighting 3 perspectives: PA as a victim, as a perpetrator, and as part of the solution. The first perspective conceptualizes PA as a victim of climate change, as heat waves, extreme weather events, and high ozone levels pose a threat to health-enhancing PA and sports; adaptation strategies are needed and potentially lifesaving. The second perspective describes PA as a perpetrator to climate change due to the significant carbon footprint of some forms of PA and sport. The third perspective focuses on PA as a solution to climate change, as some forms of PA—such as active transport and urban gardening—have both individual and planetary health benefits. In addition, PA provides health benefits in extreme situations by reducing stress and maintaining health in times of crisis. Each of these 3 perspectives can guide future research in the field of PA and health.
CRIS-Team Scopus Importer:2024-11-29
Keywords: active transport; environment; sport